Hungry Pets Visual Identity Redesign as a Representation for Middle Class Pet Shop in Penjaringan North Jakarta - Julianto; Clara Beatrice (Faculty Of Arts and Design Sebelas Maret University, 2023)
The purpose of writing Hungry Pets visual identity redesign that will to improve in terms of aesthetics, and the depiction of Hungry Pets visual identity can be more highlighted and contrasted. The balance between elements also needs to be considered in making the redesign of the Hungry Pets. The author tries to dig deeper information from various sources. So that we can further deepen information about Hungry Pets. A successful logo made from a collection of valid information and data can produce a visual element that is easy to remember. This can increase brand awareness of Hungry Pets. As well as in making the design, it is designed principles and theories. The author hopes that by writing this purpose can also obtain information that can increase public knowledge from all aspects.   Keywords: Redesign, Visual Identity, North Jakarta, Hungry Pets.